LEGAL PROTECTION OF COSMETIC CONSUMERS IN INDONESIA - anastasia tri yuli susanti (Journal Philosophy of Law, 2021)
This article is a conceptual article that will discuss how to implement legal protections for consumers in using cosmetic products based on positive law in Indonesia. This needs to be studied in a paper because it is motivated by several things. Recently the Food and Drug Supervisory Agency (from now on referred to as Badan POM [Indonesian Food and Drug Authority]) announced 27 cosmetic brands which were found to be positive for hazardous ingredients, namely Mercury (Hg), Hydroquinone, Retinoic Acid (Retinoic Acid), Rhodamine (Red K.10) and Red K.3 Mercury (Hg) dyes are both hazardous materials that can harm skin health and can cause poisoning when used for a long time. The juridical problem with law enforcement to ensure the protection of the rights of consumers of cosmetic users is that the legal construction of the protection of cosmetic users is not regulated in an existing legal provision, so that this paper will state the importance of codification, in addition, legal protection also needs to be socialized to the public to realize preventive legal protection.